Sodium, potassium food intake and global cardiovascular risks in Togo - Tchasso S. Kenao; Jerome C. Sossa; Moussiliou N. Paraiso; Mofou Belo; Ghislain E. Sopoh; Kouame M. Tchankoni; Victoire Agueh (AOSIS, 2023)
Objectives: To assess urinary sodium/potassium intake and identify its links with global cardiovascular risk (RCVG) according to the WHOPEN approach to WHO/ISH (International High Blood Pressure Society). Methods: It was a cross-sectional and analytical study that took place from July 6, 2020, to September 17, 2021, in Togo, in the Aneho, Notse and Dapaong localities. It focused on 400 adults selected by sampling. The analysis of two urine samples was done. Cardiovascular risk scores were determined from specific graphs that take into account age, gender, systolic blood pressure, diabetes status and smoking behavior. Results: Among the 400 respondents, 49% lived in rural areas. The average age was 41 (30; 51) years. The average sodium and potassium intakes were respectively 3.2 g (1.04-5.99) or 7.95 g of salt and 1.4 g (1.89-5.62) per day. The risk of excessive sodium intake was 2.39 times higher in urban areas than in rural ones (p=0.049). Residing in rural areas was associated with high potassium intakes compared to urban ones (OR=3,2 IC [1.89-5.62]). Thirteen percent (13%) of respondents were likely to develop at least a deadly or non-deadly cardiovascular disease in the next 10 years 'time, of whom 5% present a high risk. Excessive sodium intake increases by 2.10 times the risk of a deadly cardiovascular disease occurrence. Conclusions: Sodium intakes are high while potassium intakes are low with a subsequent global cardiovascular risk (GCVR) in the three cities. Sodium intakes were associated with VCVR. It is necessary to take steps to reduce excessive sodium intake and improve potassium intake.